2020
DOI: 10.37901/jcphp19-00015
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Evaluation of Clinical Pharmacy Services on Diabetes Care in an Endocrinology Clinic

Abstract: Purpose Diabetes impacts a significant population in the United States, with uncontrolled diabetes leading to serious adverse health effects and substantial cost to the healthcare system. Diabetes management by clinical pharmacy services (CPS) demonstrating positive clinical outcomes has been well-established in the primary care setting. However, there is little data evaluating the impact of CPS in specialty clinics such as endocrinology, which may provide additional opportunities for pharmacists to improve ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The impact of pharmacist-led care/programs on treatment outcomes of patients with DM is globally proven using 8,9 RCTs , but the evidence is scanty in Nigeria. The results showed that over 50% (36 out of 62) of the studies were conducted between 2015 and 2022 and approximately 98% (61 out of 62) between 2008 and 2022.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The impact of pharmacist-led care/programs on treatment outcomes of patients with DM is globally proven using 8,9 RCTs , but the evidence is scanty in Nigeria. The results showed that over 50% (36 out of 62) of the studies were conducted between 2015 and 2022 and approximately 98% (61 out of 62) between 2008 and 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies (50) were populationbased, comprising of patients with T1DM, T2DM and a few non-diabetic individuals in one pre-diabetes study, while 12 articles reported outcomes of researches conducted among community and hospital pharmacists. Fifty three studies (53) were hospital-based, while eight (8) were conducted in community pharmacies and one (1) study involved the hospital and community settings. Outcomes measures for studies retained in the review include assessment of knowledge, attitude and DM self-practice {selfmanagement or monitoring of blood glucose (SMBG)}, pharmaceutical care knowledge, practice and barriers and health related quality of life.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations